The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00428-019-02595-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed and prolonged fixation on the evaluation of immunohistochemical staining on lung carcinoma resection specimen

Abstract: Pre-analytical factors, such as fixation time, influence morphology of diagnostic and predictive immunohistochemical staining, which are increasingly used in the evaluation of lung cancer. Our aim was to investigate if variations in fixation time influence the outcome of immunohistochemical staining in lung cancer. From lung resections, specimen with tumor size bigger than 4 cm, 10 samples were obtained: 2 were put through the standard fixation protocol, 5 through the delayed, and 3 through the prolonged fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
(25 reference statements)
1
29
0
Order By: Relevance
“…One early report from the Dowsett group working with phospho‐proteins in breast cancer tissues showed that there was an almost complete loss of reactivity for p‐AKT and p‐ERK in breast resection tissues in contrast to strong staining seen in matched core biopsies from the same samples . Moreover, in a NSCLC model, delayed formalin fixation (increases in time before the start of fixation) caused significant loss of immunoreactivity : for PD‐L1, there was a reduction in the proportion of tumour cells showing positive membrane staining and the effect was larger with increase in fixation delay. In addition, (5) methods used to decalcify bony tissues and thus enable the preparation of sections from them can also significantly affect IHC results.…”
Section: Discussionmentioning
confidence: 99%
“…One early report from the Dowsett group working with phospho‐proteins in breast cancer tissues showed that there was an almost complete loss of reactivity for p‐AKT and p‐ERK in breast resection tissues in contrast to strong staining seen in matched core biopsies from the same samples . Moreover, in a NSCLC model, delayed formalin fixation (increases in time before the start of fixation) caused significant loss of immunoreactivity : for PD‐L1, there was a reduction in the proportion of tumour cells showing positive membrane staining and the effect was larger with increase in fixation delay. In addition, (5) methods used to decalcify bony tissues and thus enable the preparation of sections from them can also significantly affect IHC results.…”
Section: Discussionmentioning
confidence: 99%
“…For resection specimens, many different protocols are available, and the time from the interruption of the blood supply to the initiation of fixation is likely longer, since surgery is a more complicated procedure than CNB. It is important to adhere to good laboratory practices regarding tissue handling and fixation [ 15 ]. However, at some centres, breast resection specimens are not immediately sliced and fixed, resulting in poor fixation of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, careful assessment of pre‐analytical factors is key to avoiding false negative results when assessing 1% TPS. Investigation on the effects of pre‐analytical factors on PD‐L1 expression has been largely carried out on histological samples 20 . In fact, the only pre‐analytical data available on cytology concern the type of fixation.…”
Section: Introductionmentioning
confidence: 99%